2010
DOI: 10.1073/pnas.0914121107
|View full text |Cite
|
Sign up to set email alerts
|

Secretory IgA-mediated protection againstV. choleraeand heat-labile enterotoxin-producing enterotoxigenicEscherichia coliby rice-based vaccine

Abstract: Cholera and enterotoxigenic Escherichia coli (ETEC) are among the most common causes of acute infantile gastroenteritis globally. We previously developed a rice-based vaccine that expressed cholera toxin B subunit (MucoRice-CTB) and had the advantages of being cold chain-free and providing protection against cholera toxin (CT)-induced diarrhea. To advance the development of MucoRice-CTB for human clinical application, we investigated whether the CTB-specific secretory IgA (SIgA) induced by MucoRice-CTB gives l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 37 publications
6
110
0
2
Order By: Relevance
“…Kiyono et al demonstrated that protection against experimental enteric cholera toxin (CT) challenge following oral vaccination was dependent on SIgA [98]. pIgR was required for vaccine-mediated protection against oral CT and heat labile toxin from E. coli (LT).…”
Section: Protective Responses Against Enteric Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Kiyono et al demonstrated that protection against experimental enteric cholera toxin (CT) challenge following oral vaccination was dependent on SIgA [98]. pIgR was required for vaccine-mediated protection against oral CT and heat labile toxin from E. coli (LT).…”
Section: Protective Responses Against Enteric Pathogensmentioning
confidence: 99%
“…MucoRice is a prophylactic anti-toxic cholera vaccine that has shown promise in both murine and non-human primate preclinical studies [98,221,222]. The CTB content of each grain of MucoRice was found to be approximately 30 μg [220].…”
Section: Tablets and Capsulesmentioning
confidence: 99%
“…We previously reported that a rice-based vaccine containing the cholera toxin B subunit (MucoRice-CTB) was effective against cholera (32,33). Recently, we also introduced RNAi technology in an attempt to suppress internal storage rice protein production in order to enhance accumulation of foreign proteins in rice seed (34).…”
Section: Introductionmentioning
confidence: 99%
“…Because the duration of protective immunity is an important issue for vaccination, we examined the time course of CTB-specific serum IgG and fecal IgA antibody titers after oral immunization with MucoRice-CTB (Tokuhara et al 2010). Although the levels of CTB-specific serum IgG remained high during the 6 months after oral immunization (repeated four times) with MucoRice-CTB, fecal IgA gradually decreased and the IgA titers at six months were half the level shortly after vaccination.…”
Section: Recent Progress For the Development Of Mucorice-ctbmentioning
confidence: 99%
“…Whether MucoRice-CTB can also induce cross-protective immunity against LT is another important issue, because, as mentioned above, enteropathic E. coli is commonly found in developing countries in children (up to 63 %) with persistent diarrhea (Abba et al 2009). Oral immunization with MucoRice-CTB reduced the incidence of LT-producing enteropathic E. coli-induced diarrhea (Tokuhara et al 2010). In addition, before using MucoRice-CTB in human clinical studies, it is necessary to examine its immunogenicity and safety in nonhuman primates.…”
Section: Recent Progress For the Development Of Mucorice-ctbmentioning
confidence: 99%